(untitled) (Fiep Bulletin - online, 2011)
The traditional canoeing for all riparian people from Pará state, used by them for thousands of years to overcome their daily necessities, has been developing a lot culturally and sportively speaking. The purpose of this research has been to verify if the traditional canoeing can also be considered a sportive and cultural manifestation from Pará state. This kind of research was set as a descriptive and qualitative research that looks for the main features of the traditional canoeing and also went deeper on the cultural identity concept, allowing the building of four (4) references extracted from three great culturalistic authors: Stuart Hall (Construção Discursiva e Sentimento de Pertencimento); Benedict Anderson (Comunidades Imaginadas) and Eric Hobsbawm (Tradição Inventada). The samples were selected among the individuals from a riparian community called Aracaju, on Cachoeira do Arari town, Marajó Islands, Pará state in a total of 20 interviewed. The method used during the interviews was the structured questions and answers made possible by a questionnaire. The results according to the answers, identified four (4) references on canoeing; indicating that the sport can be considered a sportive manifestation of cultural identity from Pará state.